Charles Bendire papers - Bendire, Charles, 1836-1897.
Chiefly letters from other ornithologists and naturalists relating to Bendire's activities as honorary curator of the Museum of Natural History of the Smithsonian Institution. Correspondents include Chester Barlow, Theodore D.A. Cockerell, George Bird Grinnell, Walter Adams Johnson, Edward Avery McIlhenny, C. Hart Merriam, Otho C. Poling, William S. Ralph, Henry K. Taylor, and Ernest Seton Thompson.
Ornithologist and U.S. Army officer. Full name: Charles Emil Bendire.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Barlow, Chester, -- -1902 -- Correspondence; Cockerell, Theodore D. A. -- 1866-1948 -- Correspondence; Grinnell, George Bird, -- 1849-1938 -- Correspondence; Johnson, Walter Adams -- Correspondence; McIlhenny, Edward Avery, -- 1872-1949 -- Correspondence; Merriam, C. Hart -- 1855-1942 -- Correspondence; Poling, Otho C. -- Correspondence; Ralph, William S. -- Correspondence; Seton, Ernest Thompson, -- 1860-1946 -- Correspondence; Taylor, Henry K. -- Correspondence; National Museum of Natural History (U.S.); Ornithology; Army officers; Ornithologists